Dana Bagi Hasil dan Dana Alokasi Umum Terhadap Belanja Daerah di Propinsi Aceh - Sri Mulyati; Yusriadi Yusriadi (Agregat: Jurnal Ekonomi dan Bisnis, 2018)
This study aims to examine the effect of revenue-sharing on capital expenditures on the influence of revenue-sharing funds on district / municipal spending in Aceh. The population in this study is the Local Government Financial Statement obtained from the Regional Revenue Budget data in the form of data on revenue sharing, general allocation funds, and regional expenditure in 23 districts / cities in Aceh from 2013 until 2015 with a total population of 69 LGFS. By using multiple linear regression analysis method as data analysis method. The results of this study indicate that revenue sharing funds and general allocation funds have an effect simultaneously on local expenditures on District / City Government in Aceh. While partially, revenue sharing has significant effect to local expenditure, while general allocation fund also influences to district / city expenditure in Aceh.